A case of superficial angiomyxoma - WANG Jieyi; ZHOU Cheng; JIANG Bin; YU Bo (Pifu-xingbing zhenliaoxue zazhi, 2025)
We report a case of superficial angiomyxoma. A 25-year-old man presented with a subcutaneous mass on the left neck for one year. Dermatological examination showed a subcutaneous nodule with firm texture and moderate mobility on the neck. The ultrasound examination showed a hypoechoic area without obvious blood flow signals. Histological examination showed a mass composed of fibers, blood vessels and spindle cells, accompanied by extensive myxoid degeneration. Immunohistochemical staining showed positive for vimentin and CD34. The diagnosis was superficial angiomyxoma. Complete surgical excision was performed, and no recurrence was observed during 6-month follow-up.